PENGARUH DISIPLIN KERJA DAN MOTIVASI TERHADAP KINERJA PEGAWAI DI DINAS PARIWISATA DAERAH PROVINSI SULAWESI UTARA - Amu, Irfan; Rares, Joyce J.; Tampongangoy, Deysi (AGRI-SOSIOEKONOMI, 2022)
This study aims to determine the effect of work discipline and motivation on employee performance at the Tourism Office of North Sulawesi Province. This research was conducted from October to November 2021. The research method used was a quantitative method with an explanatory approach. Samples were taken as many as 63 respondents. This study uses multiple linear regression analysis and uses questionnaire data sourced from respondents and documentation. The results of this study indicate that the variables of work discipline and motivation have a positive and significant influence on employee performance. The percentage value of the independent variable on the dependent variable has a coefficient of determination of the stimulus (R Squere) of 0.743. This means that the rise and fall of the dependent variable, namely employee performance (Y) at the Regional Tourism Office of North Sulawesi Province is influenced by the independent variable, namely work discipline (X1) and motivation (X2) by 73.4% while the remaining 26.6 is influenced by factors others that were not investigated in this study.